2021
DOI: 10.1186/s40594-021-00275-2
|View full text |Cite
|
Sign up to set email alerts
|

Science and mathematics teacher communities of practice: social influences on discipline-based identity and self-efficacy beliefs

Abstract: Background Teacher communities of practice, identity, and self-efficacy have been proposed to influence positive teacher outcomes in retention, suggesting all three may be related constructs. Qualitative studies of communities of practice can be difficult to empirically link to identity and self-efficacy in larger samples. In this study, we operationalized teacher communities of practice as specific networks related to teaching content and/or pedagogy. This scalable approach allowed us to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Sandholtz and Ringstaff obtained positive results for teachers who worked in challenging environments, after a three-year professional development program [ 68 ]. Coupled with practice and identity, self-efficacy has positive results for teacher retention, as Polizzi et al showed, because teacher communities of practice are organized as networks [ 39 , 55 , 69 , 70 ]. Velthuis, Fisser, and Pieters found that pre-service improvement programs increased teacher self-efficacy, meaning that universities should improve their educational offer [ 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sandholtz and Ringstaff obtained positive results for teachers who worked in challenging environments, after a three-year professional development program [ 68 ]. Coupled with practice and identity, self-efficacy has positive results for teacher retention, as Polizzi et al showed, because teacher communities of practice are organized as networks [ 39 , 55 , 69 , 70 ]. Velthuis, Fisser, and Pieters found that pre-service improvement programs increased teacher self-efficacy, meaning that universities should improve their educational offer [ 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…On average, 36.6% of alters (nominated by the teachers) in a teacher's network were individuals employed at the same pre-K-12 school as the responding teacher and 21.3% were individuals employed at a different pre-K-12 school than the responding teacher. In previous social network studies of science and mathematics teachers, between one-third and one-half of alters were from the same school as the nominating teacher (Polizzi et al, 2016;Polizzi et al, 2021).…”
Section: Exploring Noyce Teachers' Support Networkmentioning
confidence: 99%
“…Teachers indicated that wellconnected networks foster collaboration among teachers, a shared vision or culture, and ease of enacting new initiatives (Polizzi et al, 2016). In a later study by Polizzi et al (2021), the authors explored mathematics and science teachers' perceptions of how connected the contacts within their networks were by showing teachers images of network maps and having them rate which map most closely resembled how connected the contacts within their own network were. Teachers' perceptions of the connections between others in their network were significantly correlated with aspects of positive science and mathematics identity (Polizzi et al, 2021).…”
Section: Noyce Teachers' Network Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…They had to spend additional time to acquire the necessary skills for working with various online platforms The issue of evaluating the teacher's effectiveness by various methods is considered in the academic literature. For example, using the Cultural-historical Activity Theory (CHAT) (McPherson & Pearce, 2022), or the Educational Process and Data Mining (EPDM) model (Okoye et al, 2020), or through the assessment of the level of teacher's identity (Polizzi et al, 2021). The academic literature survey revealed that there are no uniform international criteria for evaluating the teacher's effectiveness (Serafini, 2018;Prokopenko et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%